1994
DOI: 10.1088/0953-8984/6/35/006
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional orientational glass transitions in symmetrical difluorotetrachloroethane

Abstract: Frozen-in trans and gauche conformational disorder of symmetrical difluorotetra-chloroethane (DFTCE) produces the tendency of this plastic crystal to form an orientational glassy state on cooling below Tg=86 K. To throw light upon the freezing mechanism in DFTCE neutron diffraction and Brillouin scattering as well as infrared and dielectric measurements are employed. The overall picture of the results obtained can be characterized in terms of a classical glass-transition process with a relaxation frequency obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
16
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
8
16
0
Order By: Relevance
“…Since there are two molecules per unit cell in the bcc lattice, the molecular volume is simply a 3 /2. The zero-temperature mass density ρ (0) for the glassy crystal of each compound can be determined by extrapolating the lattice parameter to 0 K. For F-112, a (0) = 6.81 Å and hence ρ (0) = 2.14 g/cm 3 , in good agreement with previously published values, 42 and for F-113, a (0) = 6.66 Å and hence ρ (0) = 2.11 g/cm 3 . The zero-mass densities ρ (0), Debye temperatures θ D , and other basic thermodynamic data are summarized in Table I. Our F-113 specific heat measurements for all temperature ranges are shown together in Figure 3.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Since there are two molecules per unit cell in the bcc lattice, the molecular volume is simply a 3 /2. The zero-temperature mass density ρ (0) for the glassy crystal of each compound can be determined by extrapolating the lattice parameter to 0 K. For F-112, a (0) = 6.81 Å and hence ρ (0) = 2.14 g/cm 3 , in good agreement with previously published values, 42 and for F-113, a (0) = 6.66 Å and hence ρ (0) = 2.11 g/cm 3 . The zero-mass densities ρ (0), Debye temperatures θ D , and other basic thermodynamic data are summarized in Table I. Our F-113 specific heat measurements for all temperature ranges are shown together in Figure 3.…”
Section: Resultssupporting
confidence: 87%
“…42,54 The generalized Cauchy equation v 2 L (T) = A + 3v 2 T (T), which links longitudinal v L and transverse v T sound velocities, allows to determine the Debyeaveraged sound velocity v D in the zero-temperature limit. 54 Since the Debye contribution C D T 3 is calculated in the lowtemperature limit from elasto-acoustic measurements for F-112, this means that only two parameters are needed for the SPM fit at low temperature: C TLS and C sm .…”
Section: Discussionmentioning
confidence: 99%
“…The agreement of the glass temperature determined from the α-relaxation time with that from specific heat measurements and the finding of a transition of τ β (T ) into Arrhenius behavior already at τ β -values much lower than 100 s, corroborates the correct assignment of both relaxations as α-and β-relaxation. Freon112a τ dielectric [20,26] NMR [30] MD [27] TSC [31] Dielectric spectroscopy data of Krüger et al [28] and Angell [22], NMR data [33], TSC data [34] and MD data [29] are also shown. The solid and dashed lines are fits with the VFT law, eq.…”
Section: Freon112mentioning
confidence: 90%
“…Changes concerning the nature of dynamics in this system has been reported from NMR experiments, Brillouin and dielectric spectroscopy where it was suggested that the freezing process could be described on the basis of MCT [16]. MD simulations were performed for an orientationally disordered crystal sample of DFTCE at 14 different temperatures from T = 130 to 260 K in steps of 10 K and a supercooled liquid sample at 13 different temperatures from T = 150 to the melting temperature T m ≃ 300 K in steps of 10 K. The same model was used for both phases and it is completely described in [17,18].…”
mentioning
confidence: 87%
“…This compound is composed of simple molecules CFCl 2 − CFCl 2 close to dumbbells extensively used in MD calculations as prototype of molecular glass-formers liquids [15]. DFTCE plastic crystal has been experimentally widely studied and exhibits a glass transition of the overall rotation of the molecules at T g = 86 K [16].…”
mentioning
confidence: 99%